2011
DOI: 10.1159/000329626
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spine Instability following Resection of Benign Intradural Extramedullary Tumours in Children

Abstract: Background: Benign intradural extramedullary (IDEM) tumours in children are usually neural sheath derivatives or are dura based. Total resection of these benign tumours is the primary surgical goal. A management issue related to their occurrence in the growing paediatric spine is a higher propensity for the development of postlaminectomy kyphosis, especially in the upper cervical spine, than what is seen in adults. Methods: A retrospective study was performed on 22 patients to analyse the incidence, presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
7
0
2
Order By: Relevance
“…46 For those lesions affecting the foraminal regions, an additional ipsilateral facetectomy might be required. 13,24 Therefore, in view of the increased risks of spinal instability and deformities associated with these radical operations, especially when the cervical or lumbar spine is operated on, reconstructive fusion procedures are usually required. 15,19,38,39,48 One unique anatomical feature of the lamina of the lumbar spine is its relatively wide wedge-shaped interlaminar space, widest at the center while narrowed at either end.…”
mentioning
confidence: 99%
“…46 For those lesions affecting the foraminal regions, an additional ipsilateral facetectomy might be required. 13,24 Therefore, in view of the increased risks of spinal instability and deformities associated with these radical operations, especially when the cervical or lumbar spine is operated on, reconstructive fusion procedures are usually required. 15,19,38,39,48 One unique anatomical feature of the lamina of the lumbar spine is its relatively wide wedge-shaped interlaminar space, widest at the center while narrowed at either end.…”
mentioning
confidence: 99%
“…Техника и тактика лечения данной патологии разработаны в 80-х годах ХХ века [3,6,31,32]. Боль-шинство нейрохирургов рекомендуют тотальную ре-зекцию опухоли во всех возможных случаях [20,24,26,34]. Также отмечают возможность стерео-таксического радиохирургического лечения ЭМО.…”
Section: Discussionunclassified
“…Необходимость использования минимально инвазивных хирургиче-ских доступов для сохранения ортопедической ста-бильности продемонстрирована S. Furtado и соавт. [20] на основе оценки частоты послеоперационной кифотической деформации у детей после ламин-эктомии на уровне шейного отдела позвоночника.…”
Section: Discussionunclassified
“…These approaches led to problems in terms of large wounds with high infection rates and possible bleeding sources 4,17,18,23 and also predisposed patients to spinal instability 4,25 and deformities, 14,15 like the "swan neck" that was observed especially in young patients who underwent multilevel laminectomy. 7,8 This led to an increase in reports of the use of additional spinal instrumentation to solve this problem. 3,22,25,29 However, with technology advancing, several studies have indicated that it may be possible to achieve an equivalent quality of resection with minimally invasive OBJECTIVE Spinal tumors account for 2%-4% of all tumors of the central nervous system and can be intramedullary, intradural extramedullary, or extradural.…”
Section: Neurosurg Focus 43 (2):e5 2017mentioning
confidence: 99%